Age and Chronicity of Administration Dramatically Influenced the Impact of Low Dose Paraquat Exposure on Behavior and Hypothalamic-Pituitary-Adrenal Activity - Rudyk, Chris A.; McNeill, Jessica; Prowse, Natalie; Dwyer, Zach; Farmer, Kyle; Litteljohn, Darcy; Caldwell, Warren; Hayley, Shawn (Frontiers in Aging Neuroscience, 2017)
Little is known of the age-dependent and long-term consequences of low exposure levels of the herbicide and dopaminergic toxicant, paraquat. Thus, we assessed the dose-dependent effects of paraquat using a typical short-term (3 week) exposure procedure, followed by an assessment of the effects of chronic (16 weeks) exposure to a very low dose (1/10th of what previously induced dopaminergic neuronal damage). Short term paraquat treatment dose-dependently induced deficits in locomotion, sucrose preference and Y-maze performance. Chronic low dose paraquat treatment had a very different pattern of effects that were also dependent upon the age of the animal: in direct contrast to the short-term effects, chronic low dose paraquat increased sucrose consumption and reduced forced swim test immobility. Yet these effects were age-dependent, only emerging in mice older than13 months. Likewise, Y-maze spontaneous alternations and home cage activity were dramatically altered as a function of age and paraquat chronicity. In both the short and long-term exposure studies, increased corticosterone and altered hippocampal glucocorticoid receptor (GR) levels were induced by paraquat, but surprisingly these effects were blunted in the older mice. Thus, paraquat clearly acts as a systemic stressor in terms of corticoid signaling and behavioural outcomes, but that paradoxical effects may occur with: (a) repeated exposure at (b) very low doses and (c) older age. Collectively, these data raise the possibility that repeated “hits” with low doses of paraquat in combination with aging processes might have promoted compensatory outcomes.